2019
DOI: 10.1186/s12981-019-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir/cobicistat/emtricitabine/tenofovir alafenamide in treatment-experienced, virologically suppressed patients with HIV-1: subgroup analyses of the phase 3 EMERALD study

Abstract: Background Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg is a once-daily, single-tablet regimen for treatment of HIV-1 infection. The efficacy/safety of switching to D/C/F/TAF versus continuing boosted protease inhibitor (bPI) + emtricitabine/tenofovir disoproxil fumarate (control) were demonstrated in a phase 3, randomized study (EMERALD) of treatment-experienced, virologically suppressed adults through week 48. The objective of this analysis was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Subgroup analyses by previous antiretroviral use and VF showed no effect on rebound rates, virologic response, and VF rates by the FDAsnapshot analysis. 11,34 There was no exclusion on the basis of tenofovir or emtricitabine RAMs. In EMERALD D/C/F/TAF participants with previous VF (n = 98) at baseline, 37% (n = 36) had HIV-1 not fully susceptible to emtricitabine and 22% (n = 22) not fully susceptible to tenofovir (based on the genoarchive assay); baseline archived RAMs to tenofovir (4 D/C/F/TAF participants) and emtricitabine (35 D/C/F/ TAF participants, mainly 31 with M184I/V) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses by previous antiretroviral use and VF showed no effect on rebound rates, virologic response, and VF rates by the FDAsnapshot analysis. 11,34 There was no exclusion on the basis of tenofovir or emtricitabine RAMs. In EMERALD D/C/F/TAF participants with previous VF (n = 98) at baseline, 37% (n = 36) had HIV-1 not fully susceptible to emtricitabine and 22% (n = 22) not fully susceptible to tenofovir (based on the genoarchive assay); baseline archived RAMs to tenofovir (4 D/C/F/TAF participants) and emtricitabine (35 D/C/F/ TAF participants, mainly 31 with M184I/V) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Patient baseline characteristics 14,18 of the 763 patients in the D/C/F/TAF treatment arm at baseline are shown in Supplementary Table 1…”
Section: Patient Baseline Characteristicsmentioning
confidence: 99%
“…14 Antiviral efficacy was maintained through Week 96 in the D/C/F/TAF arms of both studies. 15,16 Pre-planned subgroup analyses demonstrated that D/ C/F/TAF was effective and well-tolerated through Week 48 regardless of demographic characteristics (age, gender, and race) in both studies, 17,18 clinical characteristics (baseline VL, CD4 þ cell count, and World Health Organization [WHO] clinical stage) in AMBER, 17 and prior ART experience in EMERALD. 18 The current paper reports the results of the same preplanned subgroup analyses cumulative through Week 96 in the D/C/F/TAF arms of each study.…”
Section: Introductionmentioning
confidence: 98%
“…Seven studies 2123 26 29 31 classified the gravity (grade) of AE using the DAIDS Table for Grading the Severity of Adult and Pediatric Adverse Events (from the Division of AIDS of the US Department of Health and Human Services, National Institutes of Health, National Institute of Allergy and Infectious Diseases). The others did not describe which source they used for this classification.…”
Section: Resultsmentioning
confidence: 99%